1987
DOI: 10.1002/ajpa.1330740206
|View full text |Cite
|
Sign up to set email alerts
|

Implications of tooth root hypercementosis in a Barbados slave skeletal collection

Abstract: A 17th- to 19th-century cemetery sample of 104 slaves from Newton Plantation (Barbados) shows uniquely high hypercementosis prevalence, as well as unexpectedly high and variable skeletal lead content. A variety of biological and archeological factors indicates that individuals with lower amounts of these anomalies (relative to age at death) were probably African-born, first-generation slaves. The hypercementosis is related to the progression of periodontal disease as assessed from alveolar bone. Although the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0
2

Year Published

1987
1987
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 34 publications
0
14
0
2
Order By: Relevance
“…In addition, root resorption can be caused by local factors such as chronic infection of the area, eruptive forces on neighboring teeth, traumatic injury, and cysts or tumors; however, in no present instance was there any sign of disease or trauma to the area. Corruccini et al (1987) suggested that hypercementosis may be due in part to episodes of chronic malnutrition with periodic rehabilitation, a situation that may well have characterized the Shamanka II peoples. However, there is no evidence to indicate males experienced more malnutrition (i.e., sex‐based differences in isotopic indicators of diet or dental enamel defects), implying that the primary cause is activity‐based.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, root resorption can be caused by local factors such as chronic infection of the area, eruptive forces on neighboring teeth, traumatic injury, and cysts or tumors; however, in no present instance was there any sign of disease or trauma to the area. Corruccini et al (1987) suggested that hypercementosis may be due in part to episodes of chronic malnutrition with periodic rehabilitation, a situation that may well have characterized the Shamanka II peoples. However, there is no evidence to indicate males experienced more malnutrition (i.e., sex‐based differences in isotopic indicators of diet or dental enamel defects), implying that the primary cause is activity‐based.…”
Section: Discussionmentioning
confidence: 99%
“…Chronological distributions of hypoplastic defects have been produced for several dif-ferent prehistoric and historic populations (Blakey and Armelagos, 1985;Corruccini et al, 1985;Goodman et al, 1980;Hutchinson and Larsen, 1988;Schulz and McHenry, 1975). Characteristics of the distributions have been interpreted as evidence of behavioral practices, in particular the peak ageat-stress has been associated with weaning stress (Corruccini et al, 1985;Goodman et al, 1980).…”
mentioning
confidence: 97%
“…Enamel hypoplasia, a developmental defect, has been used in recent anthropological studies as a non-specific indicator of stress (Blakey and Armelagos, 1985;Cook, 1981;Corruccini et al, 1985;Goodman et al, 1987). The defect, observed as a transverse groove or an array of pits, results from a reduction in the quantity of enamel matrix secreted (Messer, 1985;Shafer et al, 1983).…”
mentioning
confidence: 97%
See 2 more Smart Citations